Character association and genetic divergence study in elite breeding lines of groundnut (Arachis hypogaea L.): Character association and genetic divergence study in elite breeding lines of groundnut (Arachis hypogaea L.) - JAYASHREE KAR; ANKITA JENA (Journal of Oilseeds Research, 2020)
Character association and genetic divergence were carried out in a set of elite breeding lines of groundnut. Pod yield/plant showed significant positive correlation with days to first flowering, plant height, total number of gynophores/plant and 100 kernel weight both at phenotypic and genotypic level. Biological yield and harvest index had higher positive correlation as well as direct positive effect with seed yield. Thirty genotypes were distributed into eight clusters out of which four were mono-genotypic. Cluster I consisted of 16 genotypes, whereas cluster II, III and IV consisted four, four and two genotypes respectively. Cluster VIII showed highest pod yield/plant followed by cluster IV. Inter cluster distance between cluster VI and VIII was highest, whereas lowest inter cluster distance was observed between cluster III and I. Pod yield /plant contributed maximum towards genetic divergence followed by yield (q/ha).